PENEGAKAN HUKUM TERHADAP PEMBUKTIAN MENS REA DALAM TINDAK PEMBUNUHAN BERENCANA - Marsauli, Yopanus; Kristiawanto, Kristiawanto; Ismed, Mohammad (SINERGI : Jurnal Riset Ilmiah, 2025)
This research is motivated by the proof of mens rea in premeditated murder which is influenced by the approach of malicious intent and actions. The obstacles that occurred included the first instance court considering that the concept of men rea which priortized the evil intention was the first, followed by the perpetrator’s actions. This concept is adopted by the common law system which requires a long time process. These elements are alsa called dualism, while the criminal justice system in Indonesia adheres to mononism. The formulation of the problem in this research is: How is mens rea proven in premeditated murder according to the criminal code in Indonesia?and what is the concept of proving mens rea in premeditated murder according to the Indonesia Criminal Code in the future?. This research uses the Theory of Law Enforcement influenced by legal strucuture, legal substance, and legal culture and the Theory of Negative Proof, where judges can decide a person is guilty with at least two sufficient pieces of evidence and the judge’s belief that a criminal event has occorred. The type of research used by the author in this thesis is normative juridical legal research. The data obtained was then analyzed qualitatively to reach objective conlclusions. This study used secondary data from primary and secondary legal materials, analyzed descriptively. The results of the study show that firstly, the proof of mens rea in premeditated murder in Indonesia in court decisions still applies dualism, namely malicious intent and acts. Second, the Makassar court’s decision convicted a person of ordinary murder under the article on premeditated murder with the consideration of intent without planning. For the sake of the principles of legal certainty, justice and consistency in the application of the law, it is appropriate for the court to follow the decision of the Supreme Court which has permanent legal force. The House of Representatives is revising article 340 of the Criminal Code in the future regarding planning that is open to multiple interpretations. Third, the indonesian state still adheres to monotheism. Fourth, the concept of proving mens rea in premeditated murder in future actions and responbility